2012
DOI: 10.4049/jimmunol.1102954
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of NKG2D Expression by IL-4 in Memory CD8 T Cells

Abstract: IL-4 is one of the main cytokines produced during Th2-inducing pathologies. This cytokine has been shown to affect a number of immune processes such as Th differentiation and innate immune responses. However, the impact of IL-4 on CD8 T cell responses remains unclear. In this study, we analyzed the effects of IL-4 on global gene expression profiles of Ag-induced memory CD8 T cells in the mouse. Gene ontology analysis of this signature revealed that IL-4 regulated most importantly genes associated with immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 50 publications
3
37
1
Order By: Relevance
“…This finding is similar to previous results showing that IL-4 downregulated NKG2D expression on human CD8 1 T and natural killer cells and suppressed anti-tumor immune responses. [49][50][51] In our previous study, we demonstrated that CD27 1 CD25 high Vd1 T cells have a regulatory function. 40 We plan to further compare the functions of NKG2D 2 Vd1 T cells and NKG2D 1 Vd1 T cells to examine whether the NKG2D 2 Vd1 T cells have regulatory effects.…”
Section: Il-4-induced Vd1 T-cell Bias Weakened the Overall Immune Resmentioning
confidence: 99%
“…This finding is similar to previous results showing that IL-4 downregulated NKG2D expression on human CD8 1 T and natural killer cells and suppressed anti-tumor immune responses. [49][50][51] In our previous study, we demonstrated that CD27 1 CD25 high Vd1 T cells have a regulatory function. 40 We plan to further compare the functions of NKG2D 2 Vd1 T cells and NKG2D 1 Vd1 T cells to examine whether the NKG2D 2 Vd1 T cells have regulatory effects.…”
Section: Il-4-induced Vd1 T-cell Bias Weakened the Overall Immune Resmentioning
confidence: 99%
“…1A). The Elk4 Elk1 –null innate-like αβ CD8 + SP thymocyte population expressed markers associated with conventional memory cells but not IL-4–induced memory-like cells, such as NKG2D, T-bet, and CCL5 (29) (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have shown that ELK4 and ELK1 act redundantly and cell autonomously downstream of ERK signaling to limit the generation of innate-like αβ CD8 + T cells with memory characteristics in the thymus. These cells exhibit hallmarks of conventional memory CD8 + T cells, with enhanced expression of the T-box transcription factors Eomes and T-bet and increased proliferation and production of IFN-γ in response to TCR ligation (2729). The effect of ELK4 inactivation is unlikely to reflect a change in TCR repertoire that preferentially selects innate-like cells because increased innate-like αβ CD8 + differentiation occurred in Elk4 -null cells expressing the MHC class I–specific F5 TCR.…”
Section: Discussionmentioning
confidence: 99%
“…Several research groups have reported functional aspects of cytokines in which IL-2 [16,17], IL-15 [18,19] or the combination of IL-15 and TNF-α [20], have participated as key molecules, and observed a marked increased expression of the NKG2D receptor. In other studies, the dual functional role of cytokines has been demonstrated using IL-4 [21] or IL-21 [22], two well known inducers of NK cell maturation [23]. This last study suggested that both cytokines, the IL-4 and the IL-21, act as negative regulators of the NKG2D system in both NK and CD8+ T cells.…”
Section: Introductionmentioning
confidence: 88%